Report on the Measurement of International Capital Flows. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1992)
The Report evaluates statistical practices relating to the measurement of international capital flows. In particular, the principal sources of statistical descrepancies in the component categories of the capital account in the global balance of payments are addressed.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet